Acceptable Limitations on Paramedic Duty to Treat During Disaster: A Qualitative Exploration. Issue 5 (9th October 2018) - Smith, Erin; Burkle, Frederick M.; Gebbie, Kristine; Ford, David; Bensimon, Cécile
Abstract: Introduction: The Australian prehospital profession has not yet facilitated a comprehensive discussion regarding paramedic role and responsibility during disasters. Whether paramedics have a duty to treat under extreme conditions and what acceptable limitations may be placed on such a duty require urgent consideration. The purpose of this research is to encourage discussion within the paramedic profession and broader community on this important ethical and legal issue. Methods: The authors employed qualitative methods to gather paramedic and community member perspectives in Victoria, Australia. Results: These findings suggested that both paramedic and community member participants agree that acceptable limitations on paramedic duty to treat during disaster are required. These limitations should be based on consideration of the following factors: personal health circumstances (eg, pregnancy for female paramedics); pre-existing mental health conditions (eg, posttraumatic stress disorder/PTSD); competing personal obligations (eg, paramedics who are single parents); and unacceptable levels of personal risk (eg, risk of exposure and infection during a pandemic). Conclusion: It is only with the engagement of a more broadly representative segment of the prehospital profession and greater Australian community that appropriate guidance on limiting standards of care under extreme conditions can be developed and integrated within prehospital care in Australia. E Smith, FM Jr Burkle ., K Gebbie, D Ford, C Bensimon .Acceptable limitations on paramedic duty to treat during disaster: a qualitative exploration .Prehosp Disaster Med .2018 ;33 (5 ):466 –470 .